EFFECT OF DIFFERENT THERAPIES ON FERTILITY AND SERUM PROGESTERONE, METABOLITES AND MINERALS PROFILE IN REPEAT BREEDING CROSSBRED COWS - Kumar, Rajesh; Butani, M G; Dhami, A J; Kavani , F S; Shah , R G (Indian Journal of Veterinary Sciences and Biotechnology, 2009)
The study was carried out during breeding season on 31 repeat breeding and 8 normal cyclic crossbred cows to evaluate the efficacy of hormonal and antimicrobial drugs in improving fertility and its effect on serum progesterone, metabolites and macro-minerals profile. Among 10, 7 and 7 repeat breeding cows treated with 0.02 mg GnRH i/m just after AI; 500 mg of hydroxy-progesterone caproate i/m on day 4th or 5th post AI, and antibiotics (Cephalexin or ceftriaxone) i/ut 12-24 hrs post-AI, the conception rates in the treatment cycle were 60.00, 28.57 and 28.57%, respectively, as against only 14.28% in untreated control repeat breeders (n=7) and 62.50% in normal cyclic group. The results of GnRH therapy were better (P
Keywords: Repeat breeding cows; Hormonal/Antibiotics therapy; Fertility; Serum progesterone; Metabolites; Macro-minerals